Vegetable Handling, Distribution, and Wholesale Profitability in “Abinchi” Night Market, Kumasi-Ghana - Zu, K S A; Wongnaa, C A; Appiah, F (Journal of Postharvest Technology, 2014)
The study was conducted on vegetable handling practices, distribution and wholesale haulage profitability in Abinchi night market Kumasi, Ghana. Focus group discussions were held for middlemen, market queens and men, and 150 market queens and men were randomly selected and interviewed to elicit prevailing handling practices. SPSS was used to analyze data obtained and financial analytical tools; profit margin, return on investment and benefit cost ratio were used to assess the profitability of the vegetable wholesale haulage. Open and closed trucks, mini vans and taxis were identified to be regular modes of transport of vegetables. Vegetables are packed and stored in jute sacks with shelf life ranging from 3 to 7 days with visible deterioration over days. The wholesale haulage of vegetable was viable in the months of July, August and September. In mid September 2013, a 150 Kg sack full of cabbage in Tepa, a major hub of vegetable production in the Ashanti region was selling for an average of GH¢15 on farm. This constitutes 39% of the total cost of a sack full of cabbage with about 61% constituting the cost of overheads and transportation at the wholesale centre.